Analysis of Cross-Laminated Timber by Computational Homogenisation and Experimental Validation - Gonzalez-Soto, E; Saavedra-Flores, E (Elsevier Ltd, 2015)
In this paper we investigate the mechanical behaviour of cross-laminated timber panels by a computational homogenisation approach. A finite element procedure is adopted within a multi-scale modelling framework to determine the constitutive response of timber. As some of the microstructural parameters of wood are either not well-known or susceptible to considerable variation, we introduce uncertainty in the definition of the material. In order to validate the present multi-scale model, we measure experimentally the longitudinal Young s modulus and density of sawn wood beams made of radiata pine. In addition, we carry out several experimental tests on cross-laminated timber panels subject to bending, shear and compression loads. Our numerical predictions are compared with the experiments and are validated successfully, revealing the potential predictive capabilities of the present multi-scale modelling for the analysis of wood materials and timber structures. © 2014 Elsevier Ltd.